Does Activity Based Budgeting Matters? - Dwi Nita Aryani; Christian Prasetyo (Westscience Press, 2024)
This study aimed to assist AF company in reducing production costs from a financial perspective by employing Activity Based Budgeting (ABB), and to measure its performance by using non-financial perspectives namely operational efficiency, quality and time. The ABB is a tool for determining costs related to activities more accurately, as well as making the planning process more precise and corrections more effective so as to increase the company's competitive advantage. This research is a case study that AF company in Malang as the object. Data was collected by doing observation about the operational and manufacturing process, and analysing financial report year 2022. The results suggested that the company can reduce the selling price due to its lower production costs, thereby making its products more competitive in the market. This should resolve the company's main problem of declining sales. ABB can also improve teamwork among employees, budget design and the elimination of non-value-added activities. One potential benefit of an activity-based budget is that it can provide company with more accurate information regarding costs and resources needed in the work process. This result can be employed as a guideline for carrying out company activities.